Projecting expansion range of Selaginella zollingeriana in the Indonesian archipelago under future climate condition - AHMAD DWI SETYAWAN; JATNA SUPRIATNA; NISYAWATI NISYAWATI; ILYAS NURSAMSI; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO; PRAKASH PRADAN; SUGENG BUDIHARTA; ARI PITOYO; SAPTA SUHARDONO; PRABANG SETYONO; MUHAMMAD INDRAWAN (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Setyawan AD, Supriatna J, Nisyawati, Nursamsi I, Sutarno, Sugiyarto, Sunarto, Pradan P, Budiharta S, Pitoyo A, Suhardono S, Setyono P, Indrawan M. 2021. Projecting expansion range of Selaginella zollingeriana in the Indonesian archipelago under future climate conditions. Biodiversitas 22: 2088-2103. The expansion of plant species to outside areas of its original localities has attracted great interest in theoretical ecology. The scientific curiosity of such phenomenon is even deeper when the geographical expansion is confined by natural boundaries and affected by environmental changes, including climates. This study aimed to predict the current suitable habitat niche of Selaginella zollingeriana Spring, a species with original distribution in Java Island, and to project its potential suitable niche in the Indonesian archipelago accounting for future climate conditions. In doing so, we applied the Ecological Niche Modelings (ENMs) using MaxEnt algorithm by employing 30 presence data of S. zollingeriana and twelve enviro-climatic variables. The model predicted around 17.22% (22,095 km2) of the Java Island area is potentially suitable for current habitat niche of S. zollingeriana, consisting of 10.93% (14,028 km2), 4.75% (6,097 km2), and 1.54% (1,970 km2) of low, medium, and high suitability areas, respectively. Under future scenarios, the model predicted the possibility of species expansion into the other four big islands (i.e., Sumatera, Borneo, Sulawesi, and Papua). Nonetheless, the model also predicted a declining trend of the availability of suitable niches wherein from 2030 to 2080 the modeled niche declined about 58% and 59% under the most optimistic and most pessimistic climate change projections, respectively. While this study provides a primary example in predicting species expansion in tropical archipelago, similar studies in a range of contexts (e.g., species, region) are recommended to add more evidence to strengthen the theoretical ground of expansion ecology under climate changes.